1999
DOI: 10.1063/1.123782
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature crystallization of amorphous silicon using atomic hydrogen generated by catalytic reaction on heated tungsten

Abstract: A method for crystallizing amorphous silicon (a-Si) films at low temperatures is proposed. In the method, a-Si films are crystallized at temperatures lower than 400 °C by annealing in the presence of atomic hydrogen. The hydrogen atoms are generated by catalytic cracking reaction of H2 gas on a heated tungsten catalyzer in the catalytic chemical vapor deposition apparatus. It is found that the crystalline fraction of such an a-Si film is increased from 0% to several tens %, and at the same time the a-Si film i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…Thus many attempts have been made to improve film crystallinity during the initial growth of poly-/ c-Si:H on glass. [7][8][9][10] In our previous work, we have reported on high crystallinity, high quality poly-Si:H films prepared on glass from SiF 4 and H 2 gas mixtures, where a fluorinated source gas enhances crystallization and crystallite growth. 11 The film microstructures including the grain orientation are controlled by selecting appropriate deposition conditions, 12,13 which would lead to suitable device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus many attempts have been made to improve film crystallinity during the initial growth of poly-/ c-Si:H on glass. [7][8][9][10] In our previous work, we have reported on high crystallinity, high quality poly-Si:H films prepared on glass from SiF 4 and H 2 gas mixtures, where a fluorinated source gas enhances crystallization and crystallite growth. 11 The film microstructures including the grain orientation are controlled by selecting appropriate deposition conditions, 12,13 which would lead to suitable device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the thin films receive a post-growth annealing treatment with only SiF 4 and H 2 present. Using SiF 4 and H 2 in such a manner has been shown in PECVD to increase both x c and grain size [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the decomposition reactions of hydrogen molecules occurred on the heated W mesh with increasing T mesh , and atomic hydrogen was generated 21) . It has been reported that the atomic hydrogen exhibits an etching eŠect 22) . Therefore, theˆlm thickness decreased as a result of these phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…The pentaceneˆlm prepared at T mesh of 1200°C showed a meshlike texture. This implies that the surface was modiˆed by etching and the recombination reaction energy of the atomic hydrogen 22,23) on the growth surface of the pentaceneˆlm, and a unique structure, such as the meshlike texture, was formed at T mesh of 1200°C. This phenomenon is under consideration.…”
Section: Resultsmentioning
confidence: 99%